Curing of epoxy/alkyd blends in self-healing coating - Shahabudin, Nurshafiza; Yahya, Rosiyah; Gan, Seng Neon; Sonsudin, Faridah (SAGE Publications, 2018)
Self-healing of polymeric material using microcapsules has been developed to repair microcracks within the materials. The self-healing character is reflected from the curing behavior of the material. In this work, curing study of alkyd/epoxy blend was carried out by replacing part of amine hardener with alkyd in the epoxy formulation. The inclusion of alkyd in the epoxy blend resulted in higher degree of curing and higher thermal stability compared to the alkyd-free blend, as evidenced from higher heat of reaction values of differential scanning calorimetry and maximum degradation temperature at 379°C, respectively. Self-healing reaction of epoxy coating as evaluated by Fourier-transform spectroscopy revealed that the 914 cm−1 peak attributed to C–O–C of epoxy has decreased, as the epoxide group was consumed in the reaction. Appearance of a new peak at 1631–1632 cm−1 in the cured coating confirmed that the epoxide has reacted with the carboxylic acid group of alkyd to form ester.